p-Chlorophenoxyisobutyric Acid Impairs Auxin Response in Arabidopsis Root - Oono, Yutaka (The American Society for Plant Biologists, 2003)
p-Chlorophenoxyisobutyric acid (PCIB) is known as a putative antiauxin and is widely used to inhibit auxin action, although the mechanism of PCIB-mediated inhibition of auxin action is not characterized very well at the molecular level. In the present work, we showed that PCIB inhibited BA::β-glucuronidase (GUS) expression induced by indole-3-acetic acid (IAA), 2,4-dichlorophenoxyacetic acid, and 1-naphthaleneacetic acid. PCIB also inhibited auxin-dependent DR5::GUS expression. RNA hybridization and quantitative reverse transcriptase-polymerase chain reaction analyses suggested that PCIB reduced auxin-induced accumulation of transcripts of Aux/IAA genes. In addition, PCIB relieved the reduction of GUS activity in HS::AXR3NT-GUS transgenic line in which auxin inhibits GUS activity by promoting degradation of the AXR3NT-GUS fusion protein. Physiological analysis revealed that PCIB inhibited lateral root production, gravitropic response of roots, and growth of primary roots. These results suggest that PCIB impairs auxin-signaling pathway by regulating Aux/IAA protein stability and thereby affects the auxin-regulated Arabidopsis root physiology.